2018
DOI: 10.18203/2320-1770.ijrcog20183784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reid’s Combined Colposcopic Index as a predictor of cervical intraepithelial lesion

Abstract: Background: Carcinoma cervix is the commonest cancer among women worldwide and in India it accounts for 80% of all genital cancers. Screening methods include cervical cytology, human papilloma virus testing and colposcopy. Objective of present study was to evaluate suspicious cervix colposcopically using Reids Colposcopic Index (RCI) and to correlate RCI with histopathological findings.Methods: This was a prospective cross sectional study done on 125 women with clinical diagnosis of suspicious cervix. Colposco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In a study by Verma et al, the sensitivity, specificity, predictive value and false negative rate of colposcopy for invasive disease was 50%, 100%, 100% and 1.61% respectively. 9 Study by Ramadevi et al correlation between colposcopic findings and biopsy showed a good correlation for higher grade lesions (CIN Il and CIN III). 18 Sensitivity was found to be 83% and specificity was 81%.…”
Section: Correlation Between Cytology and Colposcopymentioning
confidence: 93%
See 2 more Smart Citations
“…In a study by Verma et al, the sensitivity, specificity, predictive value and false negative rate of colposcopy for invasive disease was 50%, 100%, 100% and 1.61% respectively. 9 Study by Ramadevi et al correlation between colposcopic findings and biopsy showed a good correlation for higher grade lesions (CIN Il and CIN III). 18 Sensitivity was found to be 83% and specificity was 81%.…”
Section: Correlation Between Cytology and Colposcopymentioning
confidence: 93%
“…In a study by Verma et al mean age of marriage was 20 years, and development of dysplasia had association with early marriage. 9 Study by Taherian also identified age at marriage of less than 15 years as being significantly associated with cervical cancer. 16 Early marriage before the age of 18 years could be associated with unprotected sexual exposure, early exposure to sexual activities and pregnancy at an early age which are all well known risk factors of cancer cervix.…”
Section: Correlation Between Cytology and Colposcopymentioning
confidence: 95%
See 1 more Smart Citation